PENGEMBANGAN BLENDED LEARNING BERBASIS MOODLE (STUDI KASUS DI UNIVERSITAS ISLAM RADEN RAHMAT MALANG) - Muhammad Hanif Fahmi; Bagus Seta Inba Cipta (G-Tech: Jurnal Teknologi Terapan, 2018)
E-learning is a learning method that uses the Internet, Intranet or other computer network media to deliver teaching materials to students so as to provide flexibility from the user side both lecturers and students. The weakness of e-learning is the lack of interaction between students and lecturers. If student motivation is weak, then the possibility of failure is high. From the results of identification, the problems that occur at Unira Malang at this time are the low interest of students to read the text book. In addition, some Unira Malang students are teachers and employees, so attendance is low. These problems are the foundation for researchers to develop e-learning portals to support the application of blended learning methods, namely a combination of lectures through e-learning and face-to-face lectures. The method used is the method of waterfall software development, where it describes a systematic and sequential approach to software development, starting with the specification of user needs then continuing through the stages of planning (planning), modeling (modeling), construction (construction) , testing and submission of systems to customers. E-learning is designed and implemented using Moodle's Learning Management System (LMS), which is an open source e-learning software under the GNU license that supports the implementation of blended learning. In addition to Moodle for desktops, moodle mobile has also been developed which is easily accessed through mobile phones of students and lecturers. Testing is done with the black box method, which is observing the results of execution through test data and functional checking of software. The test results show that all functions can work well, and are in accordance with the design results.